Veterinary Public Health Activities in Nebraska - Bredthauer, Annette (Kansas State University, 2011)
Activities of a state public health veterinarian.
Keywords: Veterinary; Public Health; State Public Health Veterinarian; Nebraska; Public Health (0573); Veterinary Medicine (0778)